Assessment of serum levels of MMP-8 and hs CRP in chronic periodontitis patients in relation to atherosclerotic cardiovascular disease - Raheem, Zainab J; Ahmed, Maha A (Journal of Baghdad College of Dentistry, 2014)
Background: Periodontitis and Atherosclerosis Cardiovascular disease are chronic inflammatory diseases which are highly prevalent. During the last two decades, there has been an increasing interest in the impact of oral health on atherosclerosis and subsequent cardiovascular disease.Aims of the study wereto evaluate the periodontal health status in study groups (Atherosclerotic cardiovascular disease patients with chronic periodontitis and patients having chronic periodontitis),to estimate the serum levels of Matrixmetalloproteinase-8(MMP-8) and high sensitive C-reactive protein(hs CRP) in study and control groups and compare between them. Also,test the correlation between the serum levels of MMP-8 and hs CRP with clinical periodontal parameters at each study groupSubjects, materials and methods: 80 subjects, males and females were included in this study with age range (35-50) years old, they were divided into study groups [ATH+CP group: Atherosclerotic cardiovascular disease& chronic periodontitis group (30 patients), CP group: chronic periodontitis group (30 patients)] andcontrol group: (20 systemically healthy subjects, have healthy periodontium). Periodontal health status was determined by measuring the following clinical periodontal parameters (Plaque index (PL.I), Gingival index (GI), Bleeding on probing (BOP), Probing pocket depth (PPD) and Clinical attachment level (CAL)).Serum levelsof (MMP-8and hs CRP) were determined by mean of ELISA.Results: The results showed that the mean values of clinical periodontalparameters (PL.I, GI, PPD and CAL), were higher in the ATH+CP group than in the CP group with significant differences except in PL.I there was no significant difference. A higher percentage of score 1of BOP sites demonstrated by CP groupthan in ATH+CP group with highly significant difference.The levels of serum (MMP-8 and hs CRP) were higher in ATH+CP groupwhen compared with CP group and control group, with highly significant differences between all pairs of study and control groups.Regarding the Correlation between serum levels of (MMP-8 and hs CRP) and clinical periodontal parameters, were positive correlation in both study groups.Conclusion: The present results my provide evidence that Chronic Periodontitis may contribute to the inflammation-associated to atherosclerotic process